2021
DOI: 10.3390/w13040494
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Dissolved Organic Matter by Fluorescent Analysis in a Typical River Catchment in Northern China

Abstract: Fluorescence (excitation-emission matrices, EEMs) spectroscopy coupled with PARAFAC (parallel factor) modelling and UV-Vis (ultraviolet visible) spectra were used to ascertain the sources, distribution and biogeochemical transformation of dissolved organic matter (DOM) in the Duliujian River catchment. Dissolved organic carbon (DOC), chromophoric dissolved organic matter (a335) (CDOM), and hydrophobic components (a260) were higher in summer than in other seasons with 53.3 m−1, while aromaticity (SUVA254) was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 55 publications
(118 reference statements)
1
3
0
1
Order By: Relevance
“…SUVA mean values measured in the different environments sampled (Ter River, plunged river, surface water in the reservoir, Riera Major, and effluents and impaired streams) showed no significant differences and hardly deviated from ~ 2.5 (Table 1). These values are in the lower end of figures previously reported in other systems where variability is observed (Jaffé et al 2008;Han et al 2021), and suggested low aromaticity (~ 20%, Weishaar et al 2003). The β:α ratio was homogeneous in the reservoir and in the Ter River (Fig.…”
Section: Dom Characterizationsupporting
confidence: 47%
“…SUVA mean values measured in the different environments sampled (Ter River, plunged river, surface water in the reservoir, Riera Major, and effluents and impaired streams) showed no significant differences and hardly deviated from ~ 2.5 (Table 1). These values are in the lower end of figures previously reported in other systems where variability is observed (Jaffé et al 2008;Han et al 2021), and suggested low aromaticity (~ 20%, Weishaar et al 2003). The β:α ratio was homogeneous in the reservoir and in the Ter River (Fig.…”
Section: Dom Characterizationsupporting
confidence: 47%
“…Based on the excitation-emission peak location, both autochthonous and allochthonous components were recognized. Component 1 (C1, Ex/Em = 235, 255, 295/385 nm) was categorized as terrestrial fulvic-like substances [47]. Component 2 (C2) was defined as terrestrial humic-like fluorophores (two peaks: Ex/Em = 260/460 nm and Ex/Em = 360/460 nm) [48,49].…”
Section: Optical Properties Of Fdom Componentsmentioning
confidence: 99%
“…La materia orgánica soluble presente en el agua residual (Meyo et al, 2021), tiene influencia directa sobre la conductividad eléctrica, por lo que resulta importante su evaluación en la determinación de la calidad del agua (Han et al, 2021). Al realizar la evaluación de la conductividad eléctrica, esta disminuye desde 1579 µS/cm hasta 359,35 µS/cm en el tratamiento E12V y 129 µS/cm en el tratamiento E24V (χ² = 8,366; p = 0,004), lo cual representa una eficiencia en la remoción del 77,230 % y 91,836 % respectivamente (Tabla 1).…”
Section: Metodologíaunclassified